PALACE v1.0: Paranal Airglow Line And Continuum Emission model - S. Noll; S. Noll; S. Noll; C. Schmidt; P. Hannawald; W. Kausch; S. Kimeswenger; S. Kimeswenger (Geoscientific Model Development)
Below about 2.3 µm, the nighttime emission of the Earth's atmosphere is dominated by non-thermal radiation. Excluding aurorae, the emission is caused by chemical reaction chains that are driven by the daytime photolysis and photoionisation of constituents of the middle and upper atmosphere by hard ultraviolet photons from the Sun. As this airglow can outshine even scattered moonlight in the near-infrared regime, the understanding of the Earth's night-sky brightness requires good knowledge of the complex airglow emission spectrum and its variability. However, airglow modelling is very challenging, as it would require atomic and molecular parameters, rate coefficients for chemical reactions, and knowledge of the complex dynamics at the emission heights with a level of detail that is difficult to achieve. In part, even the chemical reaction pathways remain unclear. Hence, the comprehensive characterisation of airglow emission requires large data sets of empirical data. For fixed locations, this can be best achieved by archived spectra of large astronomical telescopes with wide wavelength coverage, high spectral resolving power, and good temporal sampling. Using 10 years of data from the X-shooter echelle spectrograph in the wavelength range from 0.3 to 2.5 µm and additional data from the Ultraviolet and Visual Echelle Spectrograph at the Very Large Telescope at Cerro Paranal in Chile, we have succeeded in building a comprehensive spectroscopic airglow model for this low-latitude site with consideration of theoretical data from the HITRAN database for molecules and from different sources for atoms. The Paranal Airglow Line And Continuum Emission (PALACE) model comprises nine chemical species, 26 541 emission lines, and three unresolved continuum components. Moreover, there are climatologies of relative intensity, solar cycle effect, and residual variability with respect to local time and day of year for 23 variability classes. Spectra can be calculated with a stand-alone code for different conditions, including optional atmospheric absorption and scattering. In comparison to the observed X-shooter spectra, PALACE shows convincing agreement and is significantly better than the previous, widely used airglow model for Cerro Paranal.